A complex behavioural change intervention to reduce the risk of diabetes and prediabetes in the pre-conception period in Malaysia: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Skau, Jutta; Nordin, Awatef; Cheah, Julius; Ali, Roslinah; Zainal, Ramli; Aris, Tahir; Ali, Zainudin; Matzen, Priya; Biesma, Regien; Aagaard-Hansen, Jens; Hanson, Mark; Norris, Shane
Abstract Background Over the past two decades, the population of Malaysia has grown rapidly and the prevalence of diabetes mellitus in Malaysia has dramatically increased, along with the frequency of obesity, hyperlipidaemia and hypertension. Early-life influences play an important role in the development of non-communicable diseases. Indeed, maternal lifestyle and conditions such as gestational diabetes mellitus or obesity can affect the risk of diabetes in the next generation. Lifestyle changes can help to prevent the development of type 2 diabetes mellitus. This is a protocol for an unblinded, community-based, randomised controlled trial in two arms to evaluate the efficacy of a complex behavioural change intervention, combining motivational interviewing provided by a community health promoter and access to a habit formation mobile application, among young Malaysian women and their spouses prior to pregnancy. Method/design Eligible subjects will be Malaysian women in the age group 20 to 39 years, who are nulliparous, not diagnosed with diabetes and own a smartphone. With an alpha-value of 0.05, a statistical power of 90 %, 264 subjects will need to complete the study. Subjects with their spouses will be randomised to either the intervention or the control arm for an 8-month period. The primary endpoint is change in waist circumference from baseline to end of intervention period and secondary endpoints are changes in anthropometric parameters, biochemical parameters, change in health literacy level, dietary habits, physical activity and stress level. Primary endpoint and the continuous secondary endpoints will be analysed in a linear regression model, whereas secondary endpoints on an ordinal scale will be analysed by using the chi-squared test. A multivariate linear model for the primary endpoint will be undertaken to account for potential confounders. This study has been approved by the Medical Research and Ethics Committee of the Ministry of Health Malaysia (protocol number: NMRR-14-904-21963) on 21 September 2015. Discussion This study protocol describes the first community-based randomised controlled trial, to examine the efficacy of a complex intervention in improving the pre-pregnancy health of young Malaysian women and their spouses. Results from this trial will contribute to improve policy and practices regarding complex behavioural change interventions to prevent diabetes in the pre-conception period in Malaysia and other low- and middle-income country settings. Trial registration This trial is registered with ClinicalTrials.gov (www.clinicaltrials.gov) on 30 November 2015, Identifier:NCT02617693 .